Non-covalent interactions between molecular dimers (S66) in electric fields. (1st March 2022) - Schwilk, Max; Mezei, Pál D; Tahchieva, Diana N; von Lilienfeld, O Anatole
Abstract: Fine tuning and microscopic control of van der Waals interactions through oriented external electric fields (OEEFs) mandates an accurate and systematic understanding of intermolecular response properties. Having taken exploratory steps into this direction, we present a systematic study of interaction induced dipole electric properties of all molecular dimers in the S66 set, relying on CCSD(T)-F12b/aug-cc-pVDZ-F12 as reference level of theory. For field strengths up to ≈5 GV m −1 the interaction induced electric response beyond second order is found to be insignificant. Large interaction dipole moments (i.e. dipole moment changes due to van der Waals binding) are observed in the case of hydrogen bonding oriented along the intermolecular axis, and mostly small interaction dipole moments are found in dimers bonded by π -stacking or London dispersion. The interaction polarizabilities (i.e. polarizability changes due to van der Waals binding) were generally found to be small but always with a positive-valued principal component approximately aligned with the intermolecular axis, and two other negative-valued components. Energy decompositions according to symmetry adapted perturbation theory (SAPT0/jun-cc-pVDZ) suggest that electrostatics dominates the interaction dipole moment, with exchange and induction contributing on a smaller scale, and with dispersion having the smallest effect. First-order SAPT0 decomposition into monomer-resolved contributions enables us to establish a quantitative link between electric properties of monomers and dimers, which is found to be in qualitative agreement with the coupled cluster reference method. Using the aug-cc-pVQZ basis and non-empirical Perdew–Burke–Ernzerhof (PBE) semilocal exchange–correlation kernels, we also assess how density functional approximations in the nonlocal exchange and correlation parts affect the predictive accuracy: while dRPA@PBE0 based predictions are in excellent overall agreement with coupled cluster results, the computationally more affordable LC- ω PBE0-D3 level of theory also yields reliable results with relative errors below 5%. PBE alone, even when dispersion corrected, produces larger errors in interaction dipole moments (≈10%) and polarizabilities (≈20%). We also resolve the mutual impact of the three dimensions of the OEEF, and we present a discussion of the intermolecular distance dependence of the perturbations.